2013
DOI: 10.4103/0972-2327.107720
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon presentation of a common disorder

Abstract: We report about a young male who presented with generalized muscle stiffness, involving the limb, facial, and paraspinal muscles. The stiffness was severe enough to restrict all his daily activities, progressively increased with movements and also produced recurrent falls. This clinical picture resembled one of stiff person syndrome. As he had hypertrophy of calf muscles and generalized muscle tautness he was evaluated for other disorders which can resemble stiff person syndrome. Investigations revealed severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…A case report by Sowmini et al (2013) found a relationship between hypothyroidism and LBP. Another study by Elenius et al (2021) suggested a relationship between hyperthyroidism and LBP [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Sowmini et al (2013) found a relationship between hypothyroidism and LBP. Another study by Elenius et al (2021) suggested a relationship between hyperthyroidism and LBP [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importance of identifying such a condition is because it is completely treatable with thyroid replacement therapy and this patient could lead normal life following treatment. 53 IV. Myopathic changes are observed in 30-80% of patients with hypothyroidism.…”
Section: IIImentioning
confidence: 99%
“…Rarely, stiffness and tautness of muscles may be the only manifestation of hypothyroidism. Sowmini et al 53 reported a 30year old young male who presented with generalized muscle stiffness, involving the limbs, facial and paraspinal muscles. The stiffness was so severe that it restricted all daily activities and increased progressively with movements and produced recurrent falls.…”
Section: IIImentioning
confidence: 99%
“…Il est à noter que dans le cas de certaines maladies neuromusculaires comme celles causées par l'hypothyroïdie (Sowmini et al 2013) ou certaines neuropathies (Rowland 1985), la personne peut souffrir de douleurs et/ou crampes musculaires. La personne peut également développer des contractures et des spasmes qui induisent des mouvements involontaires, ce qui nuit à la précision du mouvement de la personne, déjà affaiblie par le manque de force musculaire.…”
Section: Faiblesse Et Fatigue Musculaireunclassified